The Challenges facing Professional Education and Practice of Academic Librarianship in the HE Sector in the UK - Rees, Emilce Sandra (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
This article examines the challenges facing professional education and practice of academic librarianship in a changing Higher Education world. Librarians in the UK, like all the professionals in the academic sector, are faced with changes in organisational mission within the university, and the changing role of information within society. Inter alia, they have to be accountable inside and outside the university and are in competition for resource allocation and funding. Against this socio-political background, the following eight challenges have been isolated: 1. recognition of librarianship as a profession (and the accreditation of library and information studies); 2. ethical professional responsibilities in a changing organisational world, and how they can be weaved into the librarian’s professional education; 3. the librarian in a changing (HE) world; 4. the “assault” on professionalism; 5. the user’s centrality: fact or fiction?; 6. the librarian in an era of global challenge: is resistance futile?; 7. Potemkin villages: fabrication and performance in the academy, and 8. feminisation of the HE professions and patterns of employment. 9. Lastly, I’ll examine future scenarios for librarians and the implications of present practices, which affect all sectors.